INTERPRESTASI HAKIM TERHADAP PERKARA PERDATA YANG TERKENA ASAS NEBIS IN IDEM - Agung Subekti (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Implementation of nebis principle in idem in lawsuit of civil case in court. The principle of nebis in idem in a civil suit lawsuit in court is applied in an earlier case that has been decided by a judge and has permanent legal force, then re-submitted for the second time with the same legal subject, object of dispute, and subject matter. Case stated nebis in idem can not be filed a second time to court unless there are differences regarding the subject of the lawsuit, the object of the case, and or the principal matter of the case.The interpretation of a judge against a civil case which may be subject to the principle of nebis in idem: That the principle of nebis in idem occurs in a case which already has permanent legal force so that no legal remedy whatsoever except the legal remedies. The criteria that must be fulfilled in order for a case to be subject to the principle of nebis in idem is that the subject of the lawsuit, the object of the case, and the subject matter must be the same as the subject of the lawsuit of the case object, and the principal matter in the case previously terminated.